2019
DOI: 10.3390/bios9010029
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Patients with Balance Insufficiency (Vestibular Hypofunction) versus Normal Subjects Using a Low-Cost Small Wireless Wearable Gait Sensor

Abstract: Balance disorders present a significant healthcare burden due to the potential for hospitalization or complications for the patient, especially among the elderly population when considering intangible losses such as quality of life, morbidities, and mortalities. This work is a continuation of our earlier works where we now examine feature extraction methodology on Dynamic Gait Index (DGI) tests and machine learning classifiers to differentiate patients with balance problems versus normal subjects on an expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Current availability of wearable sensors as well as their accuracy for measuring gait parameters [37][38][39][40] make them suitable for augmenting the information during clinical gait assessments such as FGA. Also, given the importance of head motion in both understanding vestibular processing [41][42][43][44] and diagnosing and treating vestibular disorders 15,22,25,26,[45][46][47][48][49][50][51] , we expect that this field will expand in importance over the next few years and will eventually become an integral component of clinical vestibular medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Current availability of wearable sensors as well as their accuracy for measuring gait parameters [37][38][39][40] make them suitable for augmenting the information during clinical gait assessments such as FGA. Also, given the importance of head motion in both understanding vestibular processing [41][42][43][44] and diagnosing and treating vestibular disorders 15,22,25,26,[45][46][47][48][49][50][51] , we expect that this field will expand in importance over the next few years and will eventually become an integral component of clinical vestibular medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Other IMU placements also achieved good classification performance for some of the gait tasks (AUROC 0.70) (Table 4 ). Previous studies have reported ML-based classification models based on kinematic data collected from IMUs placed on the lower limbs and/or trunk during gait for participants with vestibular deficits [ 33 , 34 ], but they have not explored upper extremity placements of IMUs. In a previous study examining the effect of IMU placement on the classification of stroke and other neurological disorders [ 36 ], a shank IMU placement resulted in better model performance compared with feet, thighs, and lower back placements.…”
Section: Discussionmentioning
confidence: 99%
“…The kinematic and spatiotemporal gait features extracted from each IMU placement are described in Table 3 . Features included ones that have been previously reported to show differences between gait patterns from individuals with vestibular deficits and controls [ 33 , 34 ] as well as features commonly used to quantify balance performance during gait.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balance disorders generate a significant healthcare burden due to the rise in hospitalization, morbidities, and mortalities in the elderly population [8]. Most of the patients who present to emergency services complain of balance disorders.…”
Section: Introductionmentioning
confidence: 99%